Starting Hemodialysis with Catheter and Mortality Risk: Persistent Association in a Competing Risk Analysis. Issue 1 (January 2016) - Roca-Tey, Ramon; Arcos, Emma; Comas, Jordi; Cao, Higini; Tort, Jaume
Purpose: The vascular access (VA) used at hemodialysis (HD) inception is involved in the mortality risk. We analyzed the survival of incident patients over time according to the initial VA and the VA profile of patients who died during the first year of follow-up. Methods: Data of VA were obtained from 9956 incident HD patients from the Catalan Registry. Results: Over 12 years, 47.9% of patients initiated HD with a fístula, 1.2% with a graft, 15.9% with a tunneled catheter and 35% with an untunneled catheter. Regarding fistula use, the hazard ratio of death for all-causes over time when applying a multivariate competing risk model was 1.55 [95% confidence interval (CI): 1.42-1.69] and 1.43 (95% CI: 1.33-1.54) for patients with tunneled and untunneled catheter, respectively. During the first year of follow-up, the crude all-cause mortality rate (deaths/100 patient-years) was higher during the early (first 120 days) compared to the late (121-365 days) period: 18.3 (95% CI: 16.8-19.8) versus 15.4 (95% CI: 14.5-16.5). Regarding fistula use, for patients using untunneled and tunneled catheter, the odds ratio of death in the early period for all-causes was 3.66 (95% CI: 2.80-4.81) and 2.97 (95% CI: 2.17-4.06), for cardiovascular causes it was 2.76 (95% CI: 1.90-4.01) and 1.84 (95% CI: 1.17-2.89) and for infection-related causes it was 6.62 (95% CI: 3.11-14.05) and 4.58 (95% CI: 2.00-10.52), respectively. Conclusions: Half of all incident patients in Catalonia are exposed to excessive mortality risk related to catheter and this scenario can be improved by early fistula placement.